Ancient Voices, Modern Echoes: The Mahabharata - Soujannya Diwan; R. Vaishnavi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Folk literature reflects the shared memory, values, and lived experiences of a society. The Mahabharata stands as one of the most powerful examples of how folk tradition and classical literature exist together in Indian culture. Although it is preserved today as a written epic, the Mahabharata was transmitted for centuries through oral storytelling, folk theatre, and regional narrations. These forms allowed the epic to reach people across social, linguistic, and educational boundaries and become part of everyday cultural life. The lasting relevance of the Mahabharata lies in its portrayal of human complexity. Its characters face moral dilemmas, emotional conflicts, and difficult choices that closely resemble real life. Rather than presenting clear divisions between good and evil, the epic explores ethical uncertainty and human weakness. This quality helped people relate to the epic and apply its lessons to their own social realities. In modern times, the Mahabharata continues to be reinterpreted through literature, theatre, and popular media. Modern retellings have focused on marginalized voices, especially women, offering new perspectives on familiar narratives. Such reinterpretations connect ancient tradition with contemporary concerns while preserving the spirit of the original epic. This paper examines the Mahabharata as a product of folk tradition, its preservation through oral culture, and its transformation through modern retellings, highlighting its enduring cultural significance.